2013
DOI: 10.1007/s00220-013-1758-2
|View full text |Cite
|
Sign up to set email alerts
|

Modular Invariance for Twisted Modules over a Vertex Operator Superalgebra

Abstract: The purpose of this paper is to generalize Zhu's theorem about characters of modules over a vertex operator algebra graded by integer conformal weights, to the setting of a vertex operator superalgebra graded by rational conformal weights. To recover SL 2 (Z)invariance of the characters it turns out to be necessary to consider twisted modules alongside ordinary ones. It also turns out to be necessary, in describing the space of conformal blocks in the supersymmetric case, to include certain 'odd traces' on mod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…Zhu proved [89] that certain trace functions on irreducible modules for suitable vertex operator algebras span representations of the modular group SL 2 (Z). More general modularity results that incorporate twisted modules have been obtained by Dong-Li-Mason [23], Dong-Zhao [28,29], and Van Ekeren [85]. We will use the extension of [89,23] to vertex operator superalgebras established in [28].…”
Section: Modularitymentioning
confidence: 99%
“…Zhu proved [89] that certain trace functions on irreducible modules for suitable vertex operator algebras span representations of the modular group SL 2 (Z). More general modularity results that incorporate twisted modules have been obtained by Dong-Li-Mason [23], Dong-Zhao [28,29], and Van Ekeren [85]. We will use the extension of [89,23] to vertex operator superalgebras established in [28].…”
Section: Modularitymentioning
confidence: 99%
“…However ω(z) equips V with noninteger conformal weights, and Zhu's theorem actually fails in this case. This situation is rectified in the reference [28], where it is shown that modular transformations map the trace functions F M to trace functions on particular twisted modules. The task becomes to relate trace functions on twisted and untwisted V -modules.…”
mentioning
confidence: 99%
“…This is achieved by the use of Li's shift operators ∆(u, z) (which appear explicitly in (1.2) above). The condition of relative cofiniteness is inspired by the work [7], and was used in [28].The transformation (1.2) was uncovered in the case of N = 2 superconformal vertex algebras in [13, Theorem 9.13 (b)], with h equal to the U (1) current of the N = 2 algebra. There the functions F M are shown to be flat sections of the bundle of conformal blocks over the universal elliptic curve, and (1.2) is derived from the geometry of this bundle.We also note that a result closely related to Theorem 1.2 was recently and independently obtained in [24] in the case of V rational and C 2 -cofinite (see also [26]).…”
mentioning
confidence: 99%
“…The importance of trace functions such as (1.14) within the broader context of modularity for super vertex operator algebras is analyzed in detail in [27]. (See also [28].…”
Section: Introductionmentioning
confidence: 99%